A New Indexing Method for Uncertain Databases - Cha, Guang-Ho (Transactions on Engineering and Computing Sciences, 2019)
This paper presents an indexing method called the uncertain data index (UD-index) for uncertain databases. The design objectives of the UD-index are improving the range query performance of the multidimensional indexing methods and providing a compromise between optimal index node clustering. Although more than ten years of database research has resulted in a great variety of multidimensional indexing methods, most efforts have focused on the data-level clustering and there has been no attempt to cluster index nodes themselves in dynamic environments. As a result, most related index nodes are widely scattered on the disk due to dynamic page allocation, and it requires many random disk accesses during the range search. The UD-index avoids that by storing the related nodes contiguously in a segment that contains a sequence of contiguous disk pages. The UD-index improves the range query performance by offering high-performance sequential disk access within a segment. A new cost model is introduced to estimate the range query performance. It takes into consideration the physical adjacency of pages read as well as the number of pages accessed. The analytic performance analysis indicates that the UD-index shows better performance than the traditional indexing methods in most cases.